Government Policy in the National Strategy for Prevent and Eradicate Corruption in State Islamic Religious Universities - Harahap, Elly Warnisyah; Zulkarnain, Zulkarnain (Letiges, 2024)
This research focuses on self-reconstruction in corruption prevention policies at State Islamic Religious Universities (PTKIN). The problem of this research is how self-reconstruction becomes a solution in corruption prevention policies to achieve justice and social welfare at PTKIN. This research proposes a self-reconstruction mechanism to prevent corruption and execute justice and social welfare at PTKIN. This research design uses a qualitative approach with case studies as the primary method. The research locations are UIN Sunan Kalijaga, UIN Syarifhidayatullah, and UIN North Sumatra Medan. The theory used in this research is the theory of self according to the Eastern/Islamic view and the theory of self according to the West, as well as the basic understanding of corruption. This study resulted in the formulation of a self-reconstruction mechanism at PTKIN in preventing corruption, namely the process of self-improvement to avoid the factors that cause corruption starting from good initial intentions, improving moral morals and then self-consistency in work. Self-reconstruction is one of the solutions to preventing corruption in PTKIN. The solution to avoid corrupt behaviour in PTKIN must involve all elements, rectors, deans, lecturers, or other components. This research provides concrete evidence about the effectiveness of the self-reconstruction mechanism in preventing corruption at PTKIN, this is a valuable finding and can be a significant contribution to the literature and practice of preventing corruption in the academic environment.